TELAAH INDEPENDENSI AUDITOR: ROTASI, ETIKA PROFESI DAN KECERDASAN EMOSIONAL - Yudawirawan, Moh. Yuddy (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Freedom is an expensive thing. Auditor valuation has an impact on company value. But the company hopes to get a good image. Therefore, the auditor sholud have integrity and professionalism. This research discusses the effect of auditor rotation, professional ethics, and emotional intelligence on auditor independence. This research method is a quantitative, because it looks for the influence of independent variables with dependent variables. This finding confirms that auditor independence is determined by rotation, professional ethics and emotional intelligence. The purpose of this finding is, to create a condition of independence, it is necessary to integrate rules, namely normative rules (Minister of Finance), professional rules (Public Accounting Firm), work rules and self-regulation